Cabozantinib for radioiodine-refractory differentiated thyroid cancer (COSMIC-311): a randomised, double-blind, placebo-controlled, phase 3 trial. Issue 8 (August 2021) - Brose, Marcia S; Robinson, Bruce; Sherman, Steven I; Krajewska, Jolanta; Lin, Chia-Chi; Vaisman, Fernanda; Hoff, Ana O; Hitre, Erika; Bowles, Daniel W; Hernando, Jorge; Faoro, Leonardo; Banerjee, Kamalika; et al.
Summary: Background: Patients with radioiodine-refractory differentiated thyroid cancer (DTC) previously treated with vascular endothelial growth factor receptor (VEGFR)-targeted therapy have aggressive disease and no available standard of care. The aim of this study was to evaluate the tyrosine kinase inhibitor cabozantinib in this patient population. Methods: In this global, randomised, double-blind, placebo-controlled, phase 3 trial, patients aged 16 years and older with radioiodine-refractory DTC (papillary or follicular and their variants) and an Eastern Cooperative Oncology Group performance status of 0 or 1 were randomly assigned (2:1) to oral cabozantinib (60 mg once daily) or matching placebo, stratified by previous lenvatinib treatment and age. The randomisation scheme used stratified permuted blocks of block size six and an interactive voice–web response system; both patients and investigators were masked to study treatment. Patients must have received previous lenvatinib or sorafenib and progressed during or after treatment with up to two VEGFR tyrosine kinase inhibitors. Patients receiving placebo could cross over to open-label cabozantinib on disease progression confirmed by blinded independent radiology committee (BIRC). The primary endpoints were objective response rate (confirmed response per Response Evaluation Criteria in Solid Tumours [RECIST] version 1.1) in the first 100 randomly assigned patients (objective response rate intention-to-treat [OITT] population) and progression-free survival (time to earlier of disease progression per RECIST version 1.1 or death) in all patients (intention-to-treat [ITT] population), both assessed by BIRC. This report presents the primary objective response rate analysis and a concurrent preplanned interim progression-free survival analysis. The study is registered with ClinicalTrials.gov, NCT03690388, and is no longer enrolling patients. Findings: Between Feb 27, 2019, and Aug 18, 2020, 227 patients were assessed for eligibility, of whom 187 were enrolled from 164 clinics in 25 countries and randomly assigned to cabozantinib (n=125) or placebo (n=62). At data cutoff (Aug 19, 2020) for the primary objective response rate and interim progression-free survival analyses, median follow-up was 6·2 months (IQR 3·4–9·2) for the ITT population and 8·9 months (7·1–10·5) for the OITT population. An objective response in the OITT population was achieved in ten (15%; 99% CI 5·8–29·3) of 67 patients in the cabozantinib group versus 0 (0%; 0–14·8) of 33 in the placebo (p=0·028) but did not meet the prespecified significance level (α=0·01). At interim analysis, the primary endpoint of progression-free survival was met in the ITT population; cabozantinib showed significant improvement in progression-free survival over placebo: median not reached (96% CI 5·7–not estimable [NE]) versus 1·9 months (1·8–3·6); hazard ratio 0·22 (96% CI 0·13–0·36; p<0·0001). Grade 3 or 4 adverse events occurred in 71 (57%) of 125 patients receiving cabozantinib and 16 (26%) of 62 receiving placebo, the most frequent of which were palmar–plantar erythrodysaesthesia (13 [10%] vs 0), hypertension (11 [9%] vs 2 [3%]), and fatigue (ten [8%] vs 0). Serious treatment-related adverse events occurred in 20 (16%) of 125 patients in the cabozantinib group and one (2%) of 62 in the placebo group. There were no treatment-related deaths. Interpretation: Our results show that cabozantinib significantly prolongs progression-free survival and might provide a new treatment option for patients with radioiodine-refractory DTC who have no available standard of care. Funding: Exelixis.